Consistency of Condom Use among Men Who Have Sex with Men as a Predictor of HIV Incidence in Indonesia - Putri Naya Apriliani; Ema Novita Deniati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Human Immunodeficiency Virus (HIV) remains a major public health concern in Indonesia, particularly among men who have sex with men (MSM), who continue to experience increasing HIV prevalence. Behavioral and structural factors, including condom use consistency, knowledge, risk perception, and access to prevention services, contribute to HIV vulnerability within this population. This study aimed to analyze the association between condom use consistency and HIV status among MSM in Indonesia, while examining the influence of demographic and behavioral confounding variables. This cross sectional study utilized secondary data from the 2019 Integrated Biological and Behavioral Surveillance (STBP), covering 2,936 MSM respondents across 13 provinces and 24 districts/cities. Data were analyzed using univariate, chi square bivariate tests, interaction analysis, and binary logistic regression to identify independent and adjusted associations between variables. A total of 20.10% of respondents were HIV reactive, and 51.75% reported inconsistent condom use. Bivariate analysis showed significant associations between HIV status and all independent and confounding variables (p < 0.05). Multivariate analysis revealed that inconsistent condom use was associated with a 29% lower likelihood of HIV infection (aOR = 0.71). Higher odds of HIV infection were observed among respondents aged ≥25 years (aOR = 1.82), unmarried or previously married (aOR = 2.79), those with a history of STI symptoms (aOR = 1.63), and those reporting difficulty accessing condoms (aOR = 1.24). Conversely, respondents who did not perceive themselves at risk (aOR = 0.51) and those who had never undergone HIV testing (aOR = 0.40) showed lower odds of HIV infection. A significant interaction was found between STI symptoms and HIV testing history (aOR = 2.18). In conclusion, condom use consistency, age, marital status, risk perception, STI symptoms, access to condoms, and HIV testing history were significantly associated with HIV status among MSM in Indonesia. Keywords: Human Immunodeficiency Virus; men who have sex with men; condom use consistency; risk factors